Exploring Integrative Islamic Religious Education and Learning Agility at Sekolah Alam Junior High School: A Phenomenological Approach to Education Innovation and Student Skill Development - Ahsan Hakim; Yus Mochamad Cholily; Khozin Khozin; M Arfan Muammar (AL-ISHLAH: Jurnal Pendidikan, 2024)
The aim of this research is to understand and discover the unique educational outcomes observed at SMP Sekolah Alam Insan Mulia (SAIM) due to the implementation of the integrative IRE model and learning agility. This research used qualitative methods and an interpretive research paradigm. This research approach used phenomenology, while the type of research was descriptive. Data collection through interviews, observations and documentation. Data analysis through data collection, data condensation, data presentation, and conclusions. This study found that SMP SAIM integrated Islamic Religious Education (PAI) into all learning to instill the foundation of Islamic values in every student's understanding and skills. The integration uses six models classified into two parts, namely the first, the shared model, the nested model, the sequenced model applied to regular learning in class. Second, the connected model, the webbed model, and the integrated model applied to large thematic projects. Furthermore, SMP SAIM carried out learning agility which was realized through project-based learning and student life skills, so that they are skilled in facing various challenges. The integrative PAI model and learning agility learning are very relevant from the flexible, active, creative, collaborative, and reflective aspects.